Response To The Growth And Production Of Criting Chili (Capsicum Annuum L.) To Liquid Organic Fertilizer Types And Concentrations - Dewi, Tyas Soemarah Koernia; Supriyadi, Teguh; Lestari, Sri Puji (Journal of Rural and Urban Community Studies, 2023)
This study aims to look at the growth and yield of curly chili plants against POC Rabbit Urine, PGPR, and Pineapple Mol with different usage concentrations in dry land. This research was conducted from August 2022 to January 2023 in Dukuh Pokoh, Musuk Village, Musuk District, Boyolali Regency. With an altitude of 845 meters above sea level. Latosol soil type. The study used the factorial method with the basic pattern of Complete Randomized Block Design (RAKL) consisting of two factors, The first type of fertilizer (M) is divided into three levels, namely: M1=Rabbit Urine, M2=PGPR and M3=Pineapple Mole. The second factor is Concentration (K) which consists of four levels namely; K0: control, K1=10ml/Lt, K2=20ml/Lt, K3 30ml/Lt. Growth parameters: plant height, plant fresh weight, and plant dry weight. Yield Parameters: Number of Green Fruits, Weight of Green Fruits, Number of Red Fruits, Weight of Red Fruits Planted, and Red Fruits per plot. The results of the study: the type of fertilizer treatment had a very significant effect on plant height, number of red fruit, weight of red fruit planted, and weight of red fruit per plot, and had no effect on the number of green fruit and weight of green fruit. POC concentration significantly affected plant height, fresh weight and dry weight of plants, number of red fruit planted, weight of red fruit per plant and per plot, and had no effect on the number of green fruit and green fruit weight. The combination of fertilizer types and concentrations had a very significant effect on plant height, plant fresh weight, plant dry weight, number of red fruit, weight of red fruit per plant, weight of red fruit per plot and had no effect on number of green fruit and weight of green fruit.